Mechanism of improvement in exercise capacity after the maze procedure combined with mitral valve surgery. Issue 1 (15th December 2003) - Yuda, S; Nakatani, S; Kosakai, Y; Satoh, T; Goto, Y; Yamagishi, M; Bando, K; Kitamura, S; Miyatake, K
Abstract : Objective: To clarify the mechanism of improvement in exercise capacity after the maze procedure. Design: Retrospective study. Setting: Tertiary referral centre. Patients: 26 patients (mean (SD) age 57 (9) years) with atrial fibrillation (AF) and mitral valve disease were studied with echocardiography and cardiopulmonary exercise testing before and after the maze procedure combined with mitral valve surgery. Of these, eight had persistent AF and 18 had restored sinus rhythm (SR) by the surgery. Six patients (mean (SD) age 59 (12) years) with AF undergoing mitral valve surgery without the maze procedure who had cardiopulmonary exercise testing before and after the surgery formed the control group. Main outcome measures: Echocardiographic parameters of atrial function were measured from transmitral flow recordings. Peak oxygen uptake (V̇o 2 ) and the slope of the relation between V̇o 2 and workload (ratio of ΔV̇o 2 to Δ work) were determined as indices of exercise capacity. Results: The degree of improvements in peak V̇o 2 and the ratio of ΔV̇o 2 to Δ work after the mitral valve surgery was comparable between the maze and control group. It was also comparable between patients with and those without successfully restored SR after the maze procedure. The degree of the increase in peak V̇o2 correlated with the change in left atrial diameter ( r = −0.40, p = 0.047) but atrial contraction did not correlate with the increase. Conclusions: Improvement in exercise capacity may not be caused by restored SR and atrial contraction but may at least partly relate to the reduction of left atrial size and improvement of haemodynamic variables by the surgery.